Efficient transport protocol and architectural design for reliable multicast in internet and prototyping using network processor - Qin, Yang (2012)
In the past years, much work has been done in addressing loss recovery problem and many transport mechanisms have been proposed. In comparison, not much mature work is done on multicast congestion control. Most of the reliable multicast schemes proposed so far do not consider congestion control issue. Owing to the underline fact of large scale, congestion control in unicast end-to-end data transmissions become more complex and challenging in multicast protocols. Due to the above changing problem, the current reliable multicast service in Internet is not mature and some outstanding issues need to be addressed. To facilitate the deployment of reliable multicast as a transport protocol, congestion control is an essential element that must be researched in greater depth.